The The Effectiveness of a Pancasila-Based Interactive Physical Education Module in Enhancing Elementary School Students' Character Values - Dewi Maya Sary; Alan Alfiansyah Putra Karo Karo; Fathir Suhada; Agus Afrizal (Jurnal Pedagogi dan Pembelajaran, 2025)
Physical Education in elementary schools still focuses on achieving motor skills, while the integration of Pancasila values has not been optimally implemented. This condition has an impact on the potential for character building through physical activity, which should be an essential part of the educational process, and is not maximized. This study aims to develop and test the effectiveness of an interactive Pancasila-based Physical Education module for elementary school students, ensuring that learning not only emphasizes physical aspects but also values and character. The research method employed a Research and Development (R&D) approach, utilizing the ADDIE model. The needs analysis involved 18 Physical Education teachers in North Sumatra. The research data analysis employed a mixed-methods approach that combines quantitative and qualitative data. The results showed that 72.2% of teachers stated they really need an interactive character-based module, 11.1% said they need it, 11.1% stated they do not need it, and 5.6% stated they do not need it. The module was prepared in print and digital formats, then validated by three experts. The effectiveness test was conducted through a one-group pre-test and post-test design on elementary school students. Quantitative data were analyzed using descriptive statistics and paired t-tests, while qualitative data were obtained through observation and interviews. Overall, the interactive Pancasila-based Physical Education module proved to be valid, practical, and effective, providing essential implications for strengthening character education in elementary schools. Consequently, the integration of Pancasila values into physical education learning can be more widely adopted to support character building.